Normative Legal Basis of Organizing Pedestrian Crossing Places - Urazimbetovich, Allayarov Nurmanbet; Kahramonovich, Khamraev Sanjar (Journal of Innovation in Education and Social Research, 2024)
The most important issue in preventing accidents related to pedestrians is the correct organization of pedestrian crossings, the speed of vehicles, the stops of directional vehicles, and the direction of pedestrians, retail trade, catering, educational institutions, industrial enterprises, administrative buildings, medical institutions, sports and entertainment institutions, recreational facilities are provided with technical solutions.